PENGARUH KEPEMILIKAN INSTITUSIONAL, KINERJA KEUANGAN, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP TAX AVOIDANCE - Salma Adellia Jauza; Neneng Hasanah (Jurnal Nusa Akuntansi, 2026)
In this study, the writer observes the influence of institutional ownership, financial performance, and environmental uncertainty on tax avoidance in Primary Consumer Goods companies listed on the Indonesia Stock Exchange (IDX) in 2020- 2024. The sampling method used in this research is the purposive sampling technique, with a quantitative research type. The data used are secondary data, namely the companies’ annual financial reports. The number of samples used in this study is 27 non-cyclical sector companies with observations for 5 (five) years, so that 135 observation objects were selected. The analysis method uses multiple linear regression, F-test, and T-test using EViews software version 13. The results of this study indicate that institutional ownership, financial performance, and environmental uncertainty simultaneously influence tax avoidance. Financial performance uncertainty partially influence tax avoidance. Meanwhile, institutional ownership and environmental uncertainty partially does not influence tax avoidance.